Tactics analysis of the top six athletes of men's 20km race in Jakarta Asian Games - Li, X.; Zhang, J.; Li, H.-L.; Li, Y.-J.; Sun, L.-X.; Wang, H.; Guo, P.-Y. (DEStech Transactions on Social Science, Education and Human Science, 2020)
This article analyzes the segmental results of the top six athletes participating in the 20km men`s walking race in the Jakarta Asian Games and the average speed change trend of each segment by using methods such as literature data and mathematical statistics. The results show that China as a whole looks at China. The overall speed distribution of athlete Wang Kaihua and Japanese athlete Shanxi Lihe is the same. They are slow first and then fast. The other four athletes are all fast first and then slow; the first six athletes basically start with the slower speed is gradually accelerating. Wang Kaihua and Shanxi Lihe have relatively good acceleration ability in the first half and speed keeping ability in the second half. The other four athletes have different degrees of speed reduction in the second half. Chinese athletes Wang Kaihua and Jin, the gold and bronze medals were won forward. Wang Kaihua adopted a speed-shifting tactic. Gold forward adopted a follow-up tactic. Silver medalist Shanxi Lihe also adopted a follow-up tactic.